ALAT PENDETEKSI SUHU TUBUH MANUSIA DENGAN SENSOR MLX90614 GY-906 BERBASIS ARDUINO UNO - Usman, Muh; Wirawan, Raden; Awal Nur, Muhammad (CV. LAJAGOE PUSTAKA, 2023)
Moment This thermometer is widely used by Public aim for prevention main transmission of the covid-19 virus. Aim study this are : (1) For designed a human body temperature detection tool using Arduino with MLX90614 GY-906 temperature sensor . (2) To find out the implementation of human body temperature detection devices in the Cafe Sawah tour. The research method used in study this is a method of research and development R&D ( Research and Development) . The design of a human body temperature detection device is carried out using a System Block Diagram. This tool is made in assembling the MLX90614 Gy-906 Sensor, Arduino Uno, 16x2 LCD, Mini DF Player, Speaker, and Resistor. Results of the implementation of the detector temperature body done with compare level accuracy with an infrared thermometer, results testing accuracy tool obtained detector temperature at a distance of 1 C cm level 99% accuracy , distance 2 C centimeters level 98.17% accuracy, distance 3 cm level accuracy 96.66%, distance 4 C centimeter level accuracy 96.24%, and a distance of 5 cm level accuracy 94.63%.